First report of the Stigmaeus diversus (Acari: Stigmaeidae) from Iran - Mojtaba Mohammad Doustaresharaf; Mohammad Bagheri (Persian Journal of Acarology)
Species of the family Stigmaeidae (Acari: Trombidiformes) live in soil and on plants in various parts of the world, are usually predators of other mites and a few prey on tree-associated arthropods or parasitize flies (Swift, 1987; Fan & Zhang, 2005). It is the largest family within the superfamily Raphignathoidea, and was established by Oudemans (1931). This family includes about 600 species in 33 valid genera (Fan et al., 2016; Doğan et al., 2017; Doğan, 2019; Akyol 2019; Khaustov 2019). The genus Stigmaeus is one of the largest and most diverse genera in the family, contains 143 valid species up to now and so far 43 species of this genus were recorded or described from Iran (Khanjani et al. 2015; Fan et al., 2016; Khaustov et al. 2017; Da-Costa et al. 2018; Akyol 2019; Majidi et al. 2019).